The Relationship Between Followership Styles And Organizational Citizenship Behavior Among Retail Sector Employees - Wafa Aina, Wahid (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study seeks to identify the relationship between followership styles and followership dimension with organization citizenship behavior. The research is conducted by using quantitative research methodology. The population is the employees in selected retails sector which is Aeon Mall Kuching and Summer Mall Kota Samarahan. The sample size was chosen based on Krejcie & Morgan’s Sample Size Determination Table. The sample size for this study is 92 respondents. This study using traditional approach by distributing the printed questionnaire to the respondents. A five-point Likert scale was used to measure all the items in the survey questionnaire. The questionnaire divided into three part, which the first part is demographic background, the second part is identify your followership styles by Kelley (1992) and the last part is Organizational citizenship Behaviour scale questionnaire (Sharma & Jain, 2014). Statistical Package for the Social Sciences (SPSS) version 20.0 had been utilized for the data analysis process. For data analysis process, Spearman’s Correlation Coefficient to test the data collected. The findings of the study revealed that there is positive relationship between the pragmatist and exemplary styles and Organization Citizenship Behavior (OCB) while there is no correlation between Alienated, Conformist and Passive styles with OCB. Furthermore, there is positive relationship between both followership dimension (active engagement and critical thinking).